Influence of the Hydrodynamic Environment on Quorum Sensing in Pseudomonas aeruginosa Biofilms - Kirisits, Mary Jo (American Society for Microbiology (ASM), 2007)
We provide experimental and modeling evidence that the hydrodynamic environment can impact quorum sensing (QS) in a Pseudomonas aeruginosa biofilm. The amount of biofilm biomass required for full QS induction of the population increased as the flow rate increased.